Mechanism of action of glatiramer acetate in multiple sclerosis and its potential for the development of new applications - Arnon, Ruth (National Academy of Sciences, 2004)
Glatiramer acetate (GA, Copaxone, Copolymer 1) is an approved drug for the treatment of multiple sclerosis and is highly effective in the suppression of experimental autoimmune encephalomyelitis in various species. The mode of action of GA is by initial strong promiscuous binding to MHC molecules and consequent competition with various myelin antigens for their presentation to T cells. A further aspect of its action is potent induction of specific suppressor cells of the T helper 2 (Th2) type that migrate to the brain and lead to in situ bystander suppression. Furthermore, the GA-specific cells in the brain express the antiinflammatory cytokines IL-10 and transforming growth factor β, in addition to brain-derived neurotrophic factor, whereas they do not express IFN-γ. Based on this immunomodulatory mode of action, we explored the potential of GA for two other applications: prevention of graft rejection and amelioration of inflammatory bowel diseases. GA was effective in amelioration of graft rejection in two systems by prolongation of skin graft survival and inhibition of functional deterioration of thyroid grafts, across minor and major histocompatibility barriers. In all transplantation systems GA treatment inhibited the detrimental secretion of Th1 inflammatory cytokines and induced beneficial Th2/3 antiinflammatory response. GA was effective also in combination with low-dose immunosuppressive drugs. Inflammatory bowel diseases are characterized by detrimental imbalanced proinflammatory immune reactivity in the gut. GA significantly suppressed the various manifestations of trinitrobenzene sulfonic acid-induced colitis, including mortality, weight loss, and macroscopic and microscopic colonic damage. GA suppressed local lymphocyte proliferations and tumor necrosis factor α detrimental secretion but induced transforming growth factor β, thus confirming the involvement of Th1 to Th2 shift in GA mode of action.